Analisis Maqashid Syariah Tentang Jual Beli Makanan Kadaluwarsa Dengan Proses Daur Ulang - Sunarsa, Sasa; Nurafifah, Neng Sovi (STAI Al Musaddadiyah Garut, 2024)
Buying and selling is a form of Muamalah that is often used by the community. The aim of the buying and selling regulations is to give freedom to humans in meeting their life needs, because human needs will not be met without a process of mutual exchange. Basically the law of buying and selling is halal, Islam does not forbid trade except trade that contains elements of injustice, evil, fraud, usury, gharar, etc. The sale and purchase must also be agreed upon between both parties, apart from that it must also be ascertained whether the sale and purchase is in conflict with maqashid sharia or not, because it is feared that it will conflict with maqashid sharia. So a problem formulation emerges: what is the production mechanism for expired food that is recycled and what is the maqashid sharia analysis regarding buying and selling expired food that is recycled. The objectives to be achieved from this research are to find out the mechanism for the production of expired food which is recycled for money and to find out the maqashid sharia analysis regarding the buying and selling of expired food which is recycled. The research method carried out by researchers is field research with a qualitative approach. Based on the results of this research, buying and selling expired food that is recycled is contrary to maintaining the soul.